In vivo combinatory gene therapy synergistically promotes cardiac function and vascular regeneration following myocardial infarction. (September 2020) - Lee, Sunghun; Park, Bong-Woo; Lee, Yong Jin; Ban, Kiwon; Park, Hun-Jun
Since myocardial infarction (MI) excessively damage the myocardium and blood vessels, the therapeutic approach for treating MI hearts should simultaneously target these two major components in the heart to achieve comprehensive cardiac repair. Here, we investigated a combinatory platform of ETV2 and Gata4, Mef2c and Tbx5 (GMT) transcription factors to develop a strategy that can rejuvenate both myocardium and vasculatures together in MI hearts. Previously ETV2 demonstrated significant effects on neovascularization and GMT was known to directly reprogram cardiac fibroblasts into cardiomyocytes under in vivo condition. Subsequently, intramyocardial delivery of a combination of retroviral GMT and adenoviral ETV2 particles into the rat MI hearts significantly increased viable myocardium area, capillary density compared to ETV2 or GMT only treated hearts, leading to improved heart function and reduced scar formation. These results demonstrate that this combinatorial gene therapy can be a promising approach to enhance the cardiac repair in MI hearts.